Functional outcome after arthroscopic mosaicplasty for localized osteochondral defects in the knee - Singh, Pravendra; Chahal, Jashandeep Singh; Aggarwal, Nipun; Kumar, Harsh (International Journal of Research in Orthopaedics, 2024)
Background: Articular cartilage is complex tissue that is able to withstand tremendous amount of force over many cycle but does not have the ability to heal even after minor injury. Treatment recommendation for articular cartilage injury and arthritis includes non-operative and operative management. Mosaicplasty is a reconstructive osteochondral grafting procedure for the treatment of articular defects of the knee. Mosaicplasty entails transplantation of small cylindrical osteochondral grafts from the non-weight bearing area of the femoral condyles and transplanting them in a mosaic like fashion into a prepared defect site on the weight-bearing surfaces of the same knee. Methods: The present study was carried out in 30 patients in our hospital prospectively to determine the functional outcome results after arthroscopic mosaicplasty for localized osteochondral defects in the knee. We conducted a prospective study on 30 patients of osteochondral defect of knee. Patients were presented with pain and recurrent swelling in the knee after sustaining twisting injury in the knee. Diagnostic arthroscopy was done and the osteochondral defects is localized and treated with mosaicplasty. The graft is harvested arthoscopically from the non-weight bearing part of the femoral condyles using a harvester. Follow up of these patients is done according to Tenger Lysholm knee scoring scale at 03 months, 06 months after surgery. Results: In our study 93.33% patients showed good to excellent results and 7% patients had fair and poor results. Conclusions: Advantage of arthroscopic mosaicplasty includes implantation of hyaline cartilage without the need for any suture or adhesive, need for smaller incision minimally invasive and very less complications. Associated injuries like ACL/PCL or meniscal tear can be addressed in the same procedure. To conclude arthroscopic mosaicplasty is excellent procedure to address the focal articular cartilage injuries of knee.